EFEKTIVITAS DISCHARGE PLANNING TENTANG PERAWATAN LUKA TERHADAP PENYEMBUHAN LUKA PADA PASIEN SECTIO CAESAREA - Basri, Basri; Wibowo, Harry Permana (Universitas Prima Indonesia, 2023)
Sectio caesarea (SC) is a surgical process to deliver a fetus through incisions made in the abdominal wall and uterus so that the fetus can be born healthy and intact. Caesarean section has life-threatening risks, one of which is the risk of infection. The quality of wound care must not decline after the patient is discharged, follow-up care at home will be very important. The aim of this study is to determine the effectiveness of discharge planning regarding wound care for wound healing in Sectio caesarea patients. This research was conducted at the BLUD of RSU Cut Nyakdhien Meulaboh. This type of research uses a quantitative method with a quasi-experimental design through a one group pre-test post-test design approach. The research population was 35 people. The sampling technique uses saturated sampling. The instrument in this study used a questionnaire filled out by respondents and observation sheets. Data analysis using univariate and bivariate. Bivariate analysis using paired t-test (Paired T-Test). The results showed that the majority of wound healing before discharge planning was carried out was good. Wound healing after the majority of discharge planning was carried out very well. The significance value of p-value = 0.000 (p <0.05) then H0 is accepted. This means that there is effectiveness of discharge planning regarding wound care for wound healing in Sectio caesarea patients. It is suggested that this study can provide additional references for future research to discuss more broadly the factors that accelerate wound healing in Sectio caesarea patients.